STRATEGI CUSTOMER RELATIONSHIPS MANAGEMENT KOMPASIANA DALAM MEMPERTAHANKAN BRAND ENGAGEMENT TERHADAP KOMPASIANER - Ade Chandra; Ardhariksa ZK Ardhariksa ZK (Jurnal Visi Komunikasi, 2020)
The Customer Relationships Management (CRM) strategy in a company or organization largely determines success in maintaining brand engagement that is inherent in the company's customers. CRM strategy is a reference that has been planned to carry out the steps of CRM activities to be carried out by the company. The study was conducted to determine the Kompasiana CRM Strategy in order to maintain brand engagement towards Kompasianer, find out the form of communication in the concept of Public Relations in the implementation of CRM and also to know Kompasiana's branding strategy to survive in competition. Research refers to some previous research relating to the concept of CRM and its impact on the company. The method used in qualitative research methods with a case study approach. While the research paradigm is post positivism, where data is obtained through in-depth interviews and observation. The results of the study showed that Kompasiana implemented a CRM strategy process consisting of Understand and Differentiate, Developed and Customized, Interact and Deliver as well as Acquire and Retain. This CRM strategy process is implemented in both online and offline activities. The form of implementation of the activities also had an impact on the image and reputation and the Kompasiana brand